ACTIVITIES OF THE FIRST LATVIAN PUBLISHERS (1860–1900) - ZANDERS, VIESTURS (Knygotyra, 2015)
The foundations for Latvian national book printing were laid down by a group of Latvian intellectuals mostly known as the movement for national liberation “Jaunlatvieši” (“New Latvians”) in the 50s and 60s of the 19th century. The „New Latvians” published several collections of popular science articles as well as Juris Alunāns’ lyrics “Dziesmiņas”. The publishing activities of Young Latvians were disturbed by the censorship as well as by the lack of financial means. In the 60s of the 19th century, the first Latvian professional publishers appeared. Heinrihs Alunāns, Kārlis Stālbergs and Klāvs Ukstiņš originally got involved in the process as authors and translators themselves, but later turned to be publishers and also owners of printing and book-selling business. The market for books in Latvian was very fragile at the time, as the Latvian publishers found it difficult to compete with the expierenced book business run by local Germans. The first generation of Latvian publishers published the first Latvian novel “Mērnieku laiki” (1879), a significant thing for Latvian literature, and translations of the world classics. At the same time they published a significant volume of low-quality literature, stimulating the incomes of publishers themselves and the reading habits of the wider audience. In the 80s of the 19th, century the first specialized publishing houses emerged. The main direction for Jānis Ozols was fiction, Kārlis Jēkabs Zihmanis published mainly books for teaching in schools. At that time, also new types of books (almanachs, collected writings, encyclopaedias) emerged.